ax-a(a+b)=-x-(-1+ab)

Simple and best practice solution for ax-a(a+b)=-x-(-1+ab) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ax-a(a+b)=-x-(-1+ab) equation:


Simplifying
ax + -1a(a + b) = -1x + -1(-1 + ab)
ax + (a * -1a + b * -1a) = -1x + -1(-1 + ab)

Reorder the terms:
ax + (-1ab + -1a2) = -1x + -1(-1 + ab)
ax + (-1ab + -1a2) = -1x + -1(-1 + ab)

Reorder the terms:
-1ab + ax + -1a2 = -1x + -1(-1 + ab)
-1ab + ax + -1a2 = -1x + (-1 * -1 + ab * -1)
-1ab + ax + -1a2 = -1x + (1 + -1ab)

Reorder the terms:
-1ab + ax + -1a2 = 1 + -1ab + -1x

Add 'ab' to each side of the equation.
-1ab + ax + ab + -1a2 = 1 + -1ab + ab + -1x

Reorder the terms:
-1ab + ab + ax + -1a2 = 1 + -1ab + ab + -1x

Combine like terms: -1ab + ab = 0
0 + ax + -1a2 = 1 + -1ab + ab + -1x
ax + -1a2 = 1 + -1ab + ab + -1x

Combine like terms: -1ab + ab = 0
ax + -1a2 = 1 + 0 + -1x
ax + -1a2 = 1 + -1x

Solving
ax + -1a2 = 1 + -1x

Solving for variable 'a'.

Reorder the terms:
-1 + ax + -1a2 + x = 1 + -1x + -1 + x

Reorder the terms:
-1 + ax + -1a2 + x = 1 + -1 + -1x + x

Combine like terms: 1 + -1 = 0
-1 + ax + -1a2 + x = 0 + -1x + x
-1 + ax + -1a2 + x = -1x + x

Combine like terms: -1x + x = 0
-1 + ax + -1a2 + x = 0

The solution to this equation could not be determined.

See similar equations:

| (3p^-4)/(9p^7) | | 3-d+-2=4-2d+-4+7 | | 3/4(16x-8)=1/2(36x-7) | | 3/4(16x-8=1/2(36x-7) | | 5/6(2x-5)=1/3 | | 0.7x^2-0.7x+4.9=0.7 | | 4-6(2-8x)=3x+4(x-9) | | 3-(5x-4)=6+2(3x-1)+x | | cosx=8 | | -3(4x+2)-x=5(2-3x)+8 | | 4(2x-8)-3x=6(3-x)+9+2x | | 6-(-2d)=-6 | | -2(3x+5)=3(6-x) | | .2y-4=.5y-7 | | 7/9x-1=6 | | 5m+3=2m+15 | | 4sin(x)cos(x)+4=0 | | 4(x+1)-9=-(2x-13) | | 57/-3 | | 3/5x-21=15 | | 13x=50 | | 5z^4-80=0 | | 3x-11+2x+6=-20 | | -6x+2=38 | | 2(5-2x)= | | z^5-80z=0 | | y=-3t^2+18t-24 | | -5X+7Y=-61 | | (x^2-5)/(16-x^2)=7 | | f(x)=x^2+12x+2 | | -5x+4=3x-9 | | -7x+y=15 |

Equations solver categories